2021
DOI: 10.1016/j.ijchp.2020.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Normal executive attention but abnormal orienting attention in individuals with sluggish cognitive tempo

Abstract: Background/objective : Sluggish Cognitive Tempo (SCT) is an attentional disorder characterized by the symptoms of slowness in behavior or thinking, a lack of en.ergy, difficulty initiating and sustaining effort, daydreaming, and drowsiness. The aim of the present study was to investigate the distinctive attentional characteristics of SCT as compared to Attention-Deficit/Hyperactivity Disorder (ADHD). Method : A total of 110 adults were recruited and divided into four groups: S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 36 publications
(30 reference statements)
0
3
0
Order By: Relevance
“…Data from 60 cross-sectional and longitudinal studies have shown that higher scores for CDS are associated with a poorer academic performance [22]. More specifically, higher CDS symptoms have been associated with: (i) poorer skills in daily life executive functioning and a greater functional impairment in the specific domains of educational activities, work, money/financial issues, managing chores and household tasks, community activities, and social situations with strangers and friends [23]; (ii) lower scores for self-organization and problem solving; (iii) higher scores for a distorted time perception [18]; (iv) a weaker orienting network due to the problems of engaging and disengaging attention [24]; (v) a reduced speed and efficacy of selective attention in early information processing [25]; (vi) more deficits in the use of self-regulated learning strategies [26]; and (vii) more difficulties in a timed reading test, although students with CDS were not slower than controls in reading comprehension, processing speed, and reading fluency [27]. On this point, more recent research has provided clearer evidence for a link between CDS and a wide range of academic [28] and neurocognitive [29] outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Data from 60 cross-sectional and longitudinal studies have shown that higher scores for CDS are associated with a poorer academic performance [22]. More specifically, higher CDS symptoms have been associated with: (i) poorer skills in daily life executive functioning and a greater functional impairment in the specific domains of educational activities, work, money/financial issues, managing chores and household tasks, community activities, and social situations with strangers and friends [23]; (ii) lower scores for self-organization and problem solving; (iii) higher scores for a distorted time perception [18]; (iv) a weaker orienting network due to the problems of engaging and disengaging attention [24]; (v) a reduced speed and efficacy of selective attention in early information processing [25]; (vi) more deficits in the use of self-regulated learning strategies [26]; and (vii) more difficulties in a timed reading test, although students with CDS were not slower than controls in reading comprehension, processing speed, and reading fluency [27]. On this point, more recent research has provided clearer evidence for a link between CDS and a wide range of academic [28] and neurocognitive [29] outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…These results proposed that the usual notion of time processing deficits in SCT result from other cognitive processes such as attention control. Kim and Kim (2020) described that groups of participants with SCT symptoms had more deficits in orienting network while the ADHD groups presented more dysfunctions in the attention executive control. Perhaps specific and different deficits in complex abilities such as executive functioning, attention, and temporal processing could explain the heterogeneity of cognitive impairments found in ADHD and SCT.…”
Section: Discussionmentioning
confidence: 99%
“…It also serves as a core construct of broader executive functions, including inhibitory control, working memory updating, and cognitive flexibility ( 21 , 29 ). Findings suggest CDS individuals may have difficulty selecting and directing attention resource to goal-relevant information, exhibiting as deficits in alerting and orienting networks ( 14 17 ). CDS may also have deficits in the ability to carry out goal-directed behavior and resolve conflicts purposefully, exhibiting as impaired efficiency in executive control of the network ( 16 ).…”
Section: Introductionmentioning
confidence: 99%